TINJAUAN PROSEDUR RENCANA KERJA DAN ANGGARAN DI SUB DIREKTORAT GLOBAL NETWORK OPERATIONS GROUP PT. TELKOMSEL - Nara Nabila Herjarema, (2023)
This final report aims to find out what the procedures for preparing the Company Work Plan and Budget (RKAP) were like at PT. Telkomsel and also has a specific purpose in writing this final project, namely as a requirement for graduating from the D3 Accounting study program at the National Veterans Development University, Jakarta. The preparation of the RKAP is useful for monitoring in determining adjustments to the implementation of a program and the budget that has been used by the company as well as for assessing the achievement of the company's performance within a predetermined period, therefore the RKAP must be ensured that it has been prepared in accordance with the policy. In preparing the RKAP PT. Telkomsel, there are parties who are responsible and have important roles. At PT. Telkomsel details the procedures for the Company's Work Plan and Budget in accordance with the company's operational policies and has used the Bestie application in its preparation to minimize errors in its implementation. The preparation of the RKAP will start from the finance section that sends official notes on the RKAP preparation up to the evaluation and validation process carried out by the IPBM department.